TI_GERICHTE 52.2018.384 vom 17. Juli 2018 , Stima ufficiale della sostanza immobiliare. Aggiornamento intermedio - TI Tribunale d'appello (2018)
Stima ufficiale della sostanza immobiliare. Aggiornamento intermedio